Consumer math and you - Rosenberg, R. Robert (Rueben Robert), 1900-; Risser, Joy (New York : Gregg Division, McGraw-Hill, 1979)
A high school textbook discussing such topics as budgeting, banking, borrowing, obtaining credit, investing, and other aspects of consumer mathematics.
Includes index.
Keywords: Finance, Personal; Consumer education